(untitled) (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Aimenova ZE, Matchanov AD, Esanov RS, Sumbembayev AA, Duissebayev SE, Dzhumanov SD, Smailov BM. 2023. Phytochemical profile of Eranthis longistipitata Regel from three study sites in the Kazakhstan part of the Western Tien Shan. Biodiversitas 24: 6031-6038. The aim of this study was to determine the phytochemical profile, the antifungal and antiradical potential of Eranthis longistipitata Regel from three study sites in the Kazakhstan part of the western Tien Shan region (in the territory of Aksu Jabagly State Nature Reserve). Sample collection was carried out in Taldybulak Gorge, Zhetymsai Gorge, and the valley of the Irsu River. The largest population of E. longistipitata was found in the valley of the Irsu River due to the high humidity and the higher availability of sunlight. The flavonoid compounds of the leaves and tubers of E. longistipitata collected in the Irsu River valley were analyzed by HPLC. Antifungal activity against Trichoderma lignorum, Fusarium oxysporum and Aspergillus niger was determined. The free radical activity was determined using DPPH. The results showed that the leaves and tubers of E. longistipitata growing in the Kazakh part of the western Tien Shan region contained rutin, apigenin, and gallic acid. The leaves of E. longistipitata had the highest rutin content (15.971 mg/g). The highest free radical scavenging activity was observed in the ethanol extract (3) of E. longistipitata leaves E. longistipitata leaves extract had good antifungal activity against F. oxysporum and A. niger (18.8 mm and 18.6 mm zones of inhibition, respectively).